Crucial role of CA cleavage sites in the cap-snatching mechanism for initiating viral mRNA synthesis - Rao, Ping (Oxford University Press, 2003)
In viral cap-snatching, the endonuclease intrinsic to the viral polymerase cleaves cellular capped RNAs to generate capped fragments that are primers for viral mRNA synthesis. Here we demonstrate that the influenza viral polymerase, which is assembled in human cells using recombinant proteins, effectively uses only CA-terminated capped fragments as primers for viral mRNA synthesis in vitro. Thus we provide the first in vitro system that mirrors the cap-snatching process occurring in vivo during virus infection. Further, we demonstrate that when a capped RNA substrate contains a CA cleavage site, the functions of virion RNA (vRNA) differ from those previously described: the 5′ terminal sequence of vRNA alone is sufficient for endonuclease activation, and the 3′ terminal sequence of vRNA functions solely as a template for mRNA synthesis. Consequently, we are able to identify the vRNA sequences that are required for each of these two separable functions. We present a new model for the influenza virus cap-snatching mechanism, which we postulate is a paradigm for the cap-snatching mechanisms of other segmented, negative-strand and ambisense RNA viruses.